Answer:
- 3) y = (7/2)x -12
- 4) y = 3x -5
- 7) y = (1/3)x +4/3
- 8) y = (-4/3)x +8/3
Explanation:
In every case, you can ...
- replace any constant in the equation by 0
- for point (h, k), replace x with (x-h) and y with (y-k), then simplify
- solve for y (add the opposite of the y-term; divide by the y-coefficient)
3) -7(x-4) +2(y-2) = 0 ⇒ -7x +2y +24 = 0
... y = (7/2)x -12
4) (y+2) = 3(x-1)
... y = 3x -5
7) -(x+4) +3(y-0) = 0 ⇒ -x +3y -4 = 0
... y = (1/3)x +4/3
8) 4(x-2) +3(y -0) = 0 ⇒ 4x +3y -8 = 0
... y = (-4/3)x +8/3